Computer-aided economic effectiveness management in applying FSM systems - Dyczkowski, Mirosław (Komputerowe wspomaganie zarządzania efektywnością ekonomiczną zastosowań systemów FSM, 2011)
The paper discusses the use of assessing Return on Investment (ROI) and Total Cost of Ownership (TCO) to manage economic effectiveness of acquiring and using IT systems.The first section introduces methodological framework for estimating ROI and TCO. Possibilities of supporting the process with the so-called ROI/TCO calculators are examined subsequently. The main section of the paper presents a case study of implementing the proposed method of analysis to manage economic effectiveness of deploying an FSM (FieldService Management) system in a hypothetical telecommunication company. The idea ofa specialized calculator and its implementation were developed in a thesis supervised by the author of this paper and written as a part of a postgraduate course in “Effective IT Managementin a Company”
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 94-108
Keywords: economic effectiveness management; ROI; TCO; ROI/TCO calculator; Field Service Management; FSM system